THEORETICAL BASIS FOR ASSESSING THE COMPETITIVENESS OF THE ENTERPRISE - HARBUZIUK, Oleksandra; RUDNICHENKO, Yevhenii; DYACHOK, Igor; SKRYPNIK, Vladislav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Enterprise competitiveness is a multifaceted concept that includes the enterprise's ability to compete effectively on the market, satisfy consumer needs, and ensure long-term sustainability. The development of competition is an integral part of economic life and the economic process, the article highlights the stages of competition development, in particular: 1) the stage of pre-capitalist competition, 2) the stage of perfect competition, 3) the stage of monopolistic competition, 4) the stage of modern competition. The article examines the essence of the concepts "competitiveness" and "enterprise competitiveness". In our opinion, competitiveness is the ability of the object of research (enterprise, product and / or service, country, etc.) to maintain and strengthen its positioning on the market compared to competitors. The study of the theoretical basis of the enterprise's competitiveness and methods of their evaluation is important for understanding the main factors affecting the enterprise's ability to compete effectively on the market. The use of various assessment methods allows businesses to identify their strengths and weaknesses, assess the competitive environment, and develop effective strategies to ensure long-term sustainability and competitive advantage. Competitiveness assessment methods are divided depending on certain parameters, including subjective and objective, qualitative and quantitative. Subjective methods are based on expert assessments and opinions of specialists, managers or other interested persons. Objective methods are based on actual data and indicators that can be measured and verified. Qualitative methods focus on the analysis of intangible aspects of the enterprise. Quantitative methods use numerical indicators to assess the competitiveness of the enterprise.
Keywords: competition; enterprise competitiveness; subjective methods; objective methods; qualitative methods; quantitative methods